2016
DOI: 10.1515/mms-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Measuring the Radiation Pattern of UHF RFID Transponders

Abstract: The operating principles of RFID antennas should be considered differently than it is applied in the classical theory of radio communication systems. The procedure of measuring the radiation pattern of antennas that could be applied to RFID transponders operating in the UHF band is seldom discussed correctly in the scientific literature. The problem consists in the variability of the RFID chip impedance that strongly influences measurement results. The authors propose the proper methodology for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…The rounded corner metal plate is placed on a assembly capable of rotating the AUT in small increments of 5 • to find the 360 • radiation pattern. A continuous wave signal from signal generator excites the AUT [29] and a PC running the test automation software which controls the measurement setup as shown in Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…The rounded corner metal plate is placed on a assembly capable of rotating the AUT in small increments of 5 • to find the 360 • radiation pattern. A continuous wave signal from signal generator excites the AUT [29] and a PC running the test automation software which controls the measurement setup as shown in Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that an axial ratio bandwidth of 12 MHz (908-920 MHz) has been successfully achieved in the proposed design [20]. Figure 9 shows the simulated and measured radiation pattern along with measured readrange that shows the proposed antenna has very good ciruclarly polarized radiation characteristics [21]. As the proposed antenna is not matched to 50 Ω therefore measurements of radiation characteristic can not be done using conventional anechoic chamber.…”
Section: Characteristics Of Antennamentioning
confidence: 98%
“…The correctness of obtained design can be confirmed by convergence of measured and calculated impedance values of inductive circuit (Table 2). This parameter has to be adjusted (after taking into account the matching circuit) to the impedance of the RFID chip input circuits (Section 8) [75,76]. It can be found in Table 2 that there is relatively good convergence (regarding the real and imaginary parts) between values of measurements for subsequent test antennas S.#1–S.#7.…”
Section: Technology Factors Affecting Synthesis Processmentioning
confidence: 99%